[PP.19.17] AORTIC RESERVOIR FUNCTION, REGIONAL ARTERIAL STIFFNESS AND AORTIC-TO-BRACHIAL STIFFNESS GRADIENT IN DIALYSIS POPULATION. (September 2017) - Fortier, C.; Desjardins, M.-P.; Sidibé, A.; Schultz, M.G.; Sharman, J.E.; Agharazii, M.
Abstract : Objective: A decreased aortic reservoir function is associated with increased cardiovascular events. Patients with chronic kidney disease in need of dialysis have an accelerated progression of aortic stiffness and reversal of the aortic-to-brachial stiffness gradient. We previously observed an annual reduction in brachial stiffness which was partly explained by a greater stiffness of the aorta. The aim of this study was to determine the relationship between aortic reservoir pressure, regional arterial stiffness and aortic-to-brachial stiffness gradient. Design and method: Among 310 patients with chronic kidney disease on dialysis, aortic and brachial stiffness were measured by determination of pulse wave velocity of carotid-femoral (cf-PWV) and carotid-radial (cr-PWV) segments (Complior). The aortic-to-brachial stiffness gradient was calculated by the ratio of cf-PWV to cr-PWV (PWV ratio). Reservoir pressure (RP), its integral (AUC-RP) and excess pressure parameters (XSP, AUC-XSP) were derived from radial pressure waveforms (radial tonometry-without generalized transfer function). Results: Reservoir pressure parameters were significantly associated with cf-PWV (stdz β of RP = 0.194, stdz β of AUC-RP = 0.168) and PWV ratio (stdz β of RP = 0.283, stdz β of AUC-RP = 0.310) in multivariate models taking into account mean arterial pressure, age, sex, hemodialysis status, diabetes, height and heart rate, all with p < 0.001. An inverse association was observed in multivariate models between reservoir pressure and cr-PWV (stdz β of RP = −0.153, stdz β of AUC-RP = −0.221). In contrast, excess pressure parameters were not significantly associated with regional stiffness and PWV ratio in multivariable models. Conclusions: In a dialysis population, aortic reservoir function was associated with aortic stiffness and PWV ratio and negatively associated with brachial stiffness in multivariate models. In contrast, no association was observed between excess pressure parameters and PWV after adjustments for potential confounders.